COVID-19: repercussions of nursing, structuring and resolutivity of national health systems - Adriana Roese Ramos; Carla Garcia Bottega; Letícia Lassen Petersen; Rosane Machado Rollo; Mariana Kliemann Marchioro; Cristianne Maria Famer Rocha (Universidade Federal do Rio Grande do Sul, 2021)
ABSTRACT Aim: To analyze the repercussions of Nursing, the structuring and resolution of National Health Systems in facing the new coronavirus (SARS-CoV-2) in selected countries. Method: Reflection article on the confrontation of COVID-19 by the National Health Systems of China, United States of America, Italy, United Kingdom, Portugal, Cuba and Brazil, from information disseminated in different media and in the literature. Results: The response of health systems depended more on political decisions than on their structuring and organization. Nursing, being the front line, was the profession most affected in number of cases and deaths. Final Considerations: The reflection shows that the countries' economic and political issues interfered in the response to COVID-19 and what the role played by Nursing is essential in the front line to face the pandemic.